2010
DOI: 10.1007/s11130-010-0192-2
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of S-allylcysteine (SAC) on Blood Glucose and Pancreatic Antioxidant System in Streptozotocin Diabetic Rats

Abstract: The aim of the present study was to evaluate the possible protective effects of S-allyl cysteine (SAC) on the antioxidant defense system of pancreas in streptozotocin(STZ) induced diabetes in rats. The levels of blood glucose and TBARS in plasma and pancreas were estimated in control and experimental groups of rats. To assess the changes in the cellular antioxidant defense system, the level of reduced glutathione in plasma and pancreas and activities of superoxide dismutase and catalase were assayed in pancrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…It has recently been reported that other sulfur compounds isolated from garlic such as thiacremonone also suppress body weight and diabetic symptoms in the livers of db/db mice. (11) Because SAC did not affect weight gain (Supplementary Fig. 1), there should be a difference in the anti-diabetic mechanisms of SAC and thiacremonone.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has recently been reported that other sulfur compounds isolated from garlic such as thiacremonone also suppress body weight and diabetic symptoms in the livers of db/db mice. (11) Because SAC did not affect weight gain (Supplementary Fig. 1), there should be a difference in the anti-diabetic mechanisms of SAC and thiacremonone.…”
Section: Discussionmentioning
confidence: 97%
“…(9,10) SAC has been shown to improve blood glucose and pancreatic oxidative stress in streptozotocin (STZ) diabetic rats, a type 1 model. (11,12) SAC and S-propyl cysteine protect STZ-induced nephropathy via nuclear factor kappa B (NFκB)-dependent anti-inflammatory effects. (13) However, it remains unclear if SAC can alleviate fatty liver in type 2 diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…For example, increased lipid peroxidation impairs membrane function by decreasing membrane fluidity and causes free-radical-induced membrane lipid peroxidation including increased membrane rigidity, decreased cellular deformability, leading to various diseases [25]. Lipid peroxidation is initiated by free radicals attack to membrane lipids, generating large amounts of reactive products, which have been implicated in diabetes and its complications.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, it has been reported that treatment with gliclazide prevented the increase level of lipid peroxidation marker in plasma and pancreas of diabetic rats. In another a study, it has been found that MDA level decreased following gliclazide treatment in patients with diabetes [25, 27]. Also, it has been reported that gliclazide may be beneficial by inhibition of lipid and protein denaturation [28].…”
Section: Discussionmentioning
confidence: 99%
“…Garlic or its preparations have been reported to possess antioxidant effects [27,28]. In addition, antioxidants have been shown to modulate oxidative stress-induced changes in hypertension, atherosclerosis and diabetes [29,30].…”
Section: Discussionmentioning
confidence: 99%